PERTANIAN PADI ORGANIK SEBAGAI SALAH SATU SOLUSI MENUJU TERWUJUDNYAKETAHANAN PANGAN DAN KESEHATAN MASYARAKAT - , Sri Aktaviyani ([Yogyakarta] : Himpunan Mahasiswa Pascasarjana UGM, 2008)
Organic Jarming is one type of agriculture system that meets the term of environmental friendly and goodfor healthy. The use of synthetic pesticide will remain its residual in its product or in the environment that will influence the public health. In addition the use of unappropriate synthetic fertilizer will degrade the soil quality consequently will decreased the quantity of yield. Oorganic farming needsmore compost, as consequent its needs more organic material supply. This fact will influence the cost production and working method that have already established.The limitation of organic supply and the availability of soil nutrient are two major elements that will determine the successfulnessand the sustainability of organic farming in the future. Implementation of rice organic farming has been evaluated in Desa Sukakarsa Kabupaten Tasikmalaya. The result showed that 50% of the respondents (farmers) feel uncomfortable with this organic agriculture system, they feel its system very complicated and unpracticed. Furthermore, Jarmers do not have enough knowledge about organic agriculture and the benefits of practicing the new method (51% of respondents). Economically, the benefit of practicing of organic Jarming with SRI system was more compelling compared to conventional agriculture system. The B/C ratio of rice organic farming was 1.97 and the BjC ratio of conventional agriculture was only 1.2. Eventually, there are severalgeneral strategies proposed in order to boost up the rice organic Jarming system in Sukakarsa village, it should be: (1) Enhance the Jarmers' knowledge about the rice organic Jarming and its benefits by optimizing the existence of groups of organic farmer